2019
DOI: 10.1007/978-3-030-35802-0_35
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Linear Layouts: Complexity, Heuristics, and Experiments

Abstract: A k-page linear graph layout of a graph G = (V, E) draws all vertices along a line and each edge in one of k disjoint halfplanes called pages, which are bounded by . We consider two types of pages. In a stack page no two edges should cross and in a queue page no edge should be nested by another edge. A crossing (nesting) in a stack (queue) page is called a conflict. The algorithmic problem is twofold and requires to compute (i) a vertex ordering and (ii) a page assignment of the edges such that the resulting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This is mostly the case for papers that distribute their dataset as supplemental material. In some cases, too, there is no ambiguity in how the graphs are generated, such as when authors use complete graphs of increasing sizes [CIW21b,CHN19,dCKN19]. In our survey we found 68 papers using custom datasets, 25% being replicable, 26.5% being reproducible, while the rest (48.5%) was non-replicable.…”
Section: Generatedmentioning
confidence: 90%
“…This is mostly the case for papers that distribute their dataset as supplemental material. In some cases, too, there is no ambiguity in how the graphs are generated, such as when authors use complete graphs of increasing sizes [CIW21b,CHN19,dCKN19]. In our survey we found 68 papers using custom datasets, 25% being replicable, 26.5% being reproducible, while the rest (48.5%) was non-replicable.…”
Section: Generatedmentioning
confidence: 90%
“…3. Finally, we mention the possibility of studying the parameterized complexity of mixed linear layouts, using both queues and stacks, see [6,16,21,25].…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…We conclude with an algorithmic question, namely, what is the complexity of recognizing graphs that admit mixed 1-stack 1-queue layouts, even for 2-trees? Note that recently de Col et al [9] showed that testing whether a (not necessarily planar) graph admits a mixed 2-stack 1-queue layout is NP-complete.…”
Section: Open Problemsmentioning
confidence: 99%